Nuclear receptors in the kidney during health and disease. (April 2021) - Libby, Andrew E.; Jones, Bryce; Lopez-Santiago, Isabel; Rowland, Emma; Levi, Moshe
Abstract: Over the last 30 years, nuclear receptors (NRs) have been increasingly recognized as key modulators of systemic homeostasis and as contributing factors in many diseases. In the kidney, NRs play numerous important roles in maintaining homeostasis—many of which continue to be unraveled. As "master regulators", these important transcription factors integrate and coordinate many renal processes such as circadian responses, lipid metabolism, fatty acid oxidation, glucose handling, and inflammatory responses. The use of recently-developed genetic tools and small molecule modulators have allowed for detailed studies of how renal NRs contribute to kidney homeostasis. Importantly, while NRs are intimately involved in proper kidney function, they are also implicated in a variety of renal diseases such as diabetes, acute kidney injury, and other conditions such as aging. In the last 10 years, our understanding of renal disease etiology and progression has been greatly shaped by knowledge regarding how NRs are dysregulated in these conditions. Importantly, NRs have also become attractive therapeutic targets for attenuation of renal diseases, and their modulation for this purpose has been the subject of intense investigation. Here, we review the role in health and disease of six key renal NRs including the peroxisome proliferator-activated receptors (PPAR), estrogen-related receptors (ERR), the farnesoid X receptors (FXR), estrogen receptors (ER), liver X receptors (LXR), and vitamin D receptors (VDR) with an emphasis on recent findings over the last decade. These NRs have generated a wealth of data over the last 10 years that demonstrate their crucial role in maintaining normal renal homeostasis as well as their capacity to modulate disease progression.